2021
DOI: 10.17933/jppi.v11i1.341
|View full text |Cite
|
Sign up to set email alerts
|

Online Shopper Intention Analysis Using Conventional Machine Learning And Deep Neural Network Classification Algorithm

Abstract: The use of e-commerce throughout the world in recent years is very rapid. The continuous increase in sales shows that e-commerce has huge market potential. Store profits are derived from the process of assessing data to identify and classify online shopper intentions. The process of assessing the data uses conventional machine learning algorithms and deep neural networks. Comparison of algorithms in this study using the python programming language by knowing the value of Accuracy, F1-Score, Precision, Recall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…where σ is the sigmoid activation function, a randomly initialized weight matrix W 1 , W 2 is used to map h t , h i into the hidden vector space, and the computed results of the function q are fed into the softmax function for normalization to obtain the weights of each hidden state α. e last step of BiGRU, hidden state h t , is calculated from the last input and the hidden state of the previous state, which can be abstractly understood as the current point of interest or short-term behavioral preferences of the e-commerce user, while the output c t of the attention module is the information extraction for the whole sequence of behaviors, and since the module adaptively focuses on those e-commerce user behaviors that are more important, such as being able to learn that the sequence of e-commerce users clicking on swimming gear is more important, therefore, c t contains the main intention of the e-commerce user during the current behavior, that is, the long-term behavioral preferences of the current sequence. By combining the short-term behavioral preferences h t and long-term behavioral preferences c t of e-commerce users in the current behavior sequence for learning and prediction, not only does it alleviate the problem of losing important information caused by encoding the input sequence as a fixed-length vector by the encoder and making full use of the sequence input information but also allows the model to focus on both the long-term and short-term preferences of e-commerce users in the current sequence, which can improve the prediction effect well [21][22][23].…”
Section: Principle Of Extracting E-commerce Users' Intention Bymentioning
confidence: 99%
“…where σ is the sigmoid activation function, a randomly initialized weight matrix W 1 , W 2 is used to map h t , h i into the hidden vector space, and the computed results of the function q are fed into the softmax function for normalization to obtain the weights of each hidden state α. e last step of BiGRU, hidden state h t , is calculated from the last input and the hidden state of the previous state, which can be abstractly understood as the current point of interest or short-term behavioral preferences of the e-commerce user, while the output c t of the attention module is the information extraction for the whole sequence of behaviors, and since the module adaptively focuses on those e-commerce user behaviors that are more important, such as being able to learn that the sequence of e-commerce users clicking on swimming gear is more important, therefore, c t contains the main intention of the e-commerce user during the current behavior, that is, the long-term behavioral preferences of the current sequence. By combining the short-term behavioral preferences h t and long-term behavioral preferences c t of e-commerce users in the current behavior sequence for learning and prediction, not only does it alleviate the problem of losing important information caused by encoding the input sequence as a fixed-length vector by the encoder and making full use of the sequence input information but also allows the model to focus on both the long-term and short-term preferences of e-commerce users in the current sequence, which can improve the prediction effect well [21][22][23].…”
Section: Principle Of Extracting E-commerce Users' Intention Bymentioning
confidence: 99%
“…An open-source project called Gradient Boosting uses the greedy function approach to create the gradient tree boosting machine learning system, which is effective, quick, and scalable for solving various learning problems. In supervised learning problems, XGBoost predicts the goal variable yi using training data with multiple features xi (Cucu Ika Agustyaningrum, Haris, Aryanti, & Misriati, 2021). f. Support Vector Machine Support Vector Machine (SVM) is an integrated (supervised) classification method that needs specific learning goals during training (Nurachim, 2019).…”
Section: Ada Boostmentioning
confidence: 99%
“…A few studies have investigated classical machine learning approaches as alternatives to deep learning. Agustyaningrum et al [7] found that XGBoost outperformed DNNs and CNNs for monkeypox prediction. Maqsood et al [8] used a support vector machine (SVM) on features extracted from Inception-ResNet and NASNet models.…”
Section: Literature Surveymentioning
confidence: 99%